Factors Contributing to Increased Stress among Bedside Nurses Working in Tertiary Care Hospitals in Karachi, Pakistan - Khair-Un-Nisa Khan, Dua Zafar, Nida Tanveer, Sanam Urooj, Uzma Usman, Cinderella Peter, Shahla Pardhan (Pakistan Journal of Medical & Health Sciences, 2025)
Introduction: Nurses are facing stress due to work related factors which highly impacting their career by suffering from heavy workloads, insufficient staffing, turnover, limited resources, and the prolong duties hours which elevated their stress respectively into their profession. Objective: To determine the factors contributing to increased stress amongst bedside nurses working in public and private tertiary care hospitals at Karachi, Pakistan. Methodology: An analytical Cross-sectional study was conducted in both Public Dr. Ruth K. M. Pfau, Civil Hospital Karachi, and Private Kharadar General Hospital (KGH) where data were collected amongst 200 nurses, from June to August, 2024, and Convenient sampling technique was used to assess the self-structured questionnaire from RN, BSN, MSN whereas, RM, CMW, CHN, LHV, and nursing students were not included in this study setting. Results: The results revealed that, stress amongst nurses were identified more on female 126 (63%), unmarried124 (62%) women whose age between 20-30 86(43%), residing in urban 172(86%) Muslim 127(63.5), Punjabi 84(42.5%), had BSN degree 64(32%) mainly were from 40(20%) from medical department than other units, were suffering more stress from; clinical environment 133 (66.5%), lack of support from nursing administration 140(70%), miscommunication between health care provider (colleagues or doctors) 151(75.5%), making mistake in treating patient153(76.5%), doctors commanding 141(70.5%),shortage of healthcare provider in emergency situation163(81.5%), pressure from unit managers, doctors and supervisors 113(56.5%), by working constantly doing night shift duties 128(64%), having additional responsibility and long working hours by the management 138(69%), ineffective or unsupportive may create a negative work environment 160(80%), lack of professional development opportunities; training, educational facilities, promotion 155(77.5%), lack of safety and security139(69.5%), busy by the paper work and documentation 152(76%). Herein, X2 test also used to evaluate the association between the factors and the socio demographic variables in which hospitals, age, gender, religion and ethnicity were highly significantly associated as (P-value< 0.05) Conclusion: The nursing profession is comprises the stress of bedside nurses which directly impacts on nurse’s health, patient-care, and health system of the country. Keywords: Nurses, Stress, Workload, Lack of Support from Nursing Administration, Shortage of HealthCare Provider.